Seroepidemiology of Crimean Congo Hemorrhagic Fever in Slaughterhouse Workers in North Eastern Iran - M Zeinali; N Bayat; M Moradi; SM J Parizadeh; A Hezareh Moghadam; S Chinikar; E Mostafavi (Iranian Journal of Public Health, 2012)
Background: Crimean Congo Hemorrhagic Fever (CCHF) is an acute febrile haemorrhagic disease. This study was conducted to ascertain the infection status amongst slaughterhouse workers in Iran's north-eastern provinces (Razavi and northern and southern Khorasan), so that analysis of the results could help clarification of the epidemiology of this disease in the aforementioned provinces and eastern regions of Iran.Methods: In this cross-sectional study, conducted in 2004 and 2005, 108 slaughterhouse workers from 24 cities of the three previously mentioned provinces were randomly entered into the study. An IgG specific ELISA test was carried out on the participants’ serum samples.Results: Sixteen out of 108 (14.8%) participants under study were shown to have IgG against CCHF. The highest rate of infection was seen in Razavi Khorasan and southern Khorasan at 17.5% and 16.7%, respectively.Conclusion: The study showed a relatively high frequency of this disease amongst slaughterhouse workers in these provinces. Taking into account the small number of reported cases from these provinces, it would seem that more focus is required on primary diagnosis and on referral of suspected patients.